A Comparative Study on Preference Towards Intraday & Long-Term Investment in Stock Market Among Gen-Z in Ahmedabad City - Purohit, Vraj; Shah, Kunj; Vidani, Jignesh (International Journal of Economic, Finance and Business Statistics, 2024)
This study elaborates on the investment preference of Gen Z in Ahmedabad in terms of the comparative inclination towards intraday trading and long-term investing in the stock market. The research discovers key factors that influence these preferences: Their perception of the potential to build wealth, confidence in the decision-making process, an understanding of risk tolerance, and the role of technology as well as social media. A structured hypothesis-testing approach revealed that the investment preference is, in fact very long-term, a perception of stability and more effective wealth accumulation rather than the high-risk, high-reward nature of intraday trading. Confidence in making informed decisions, especially in intraday trading, "Tends to be confounded with age and financial knowledge," whereas "Technological tools decisively shape investment choices”. The second influence is social media and online forums, as young investors obtain their information and guidance from many such portals. The practical implications of the present study suggest that financial institutions should constantly promote long-term investment products and enrich digital platforms to cater to the tech-savvy investor belonging to the Gen Z category. Future studies can analyse the shifts in preferences of such a crowd, the role of financial literacy and the effects of new technologies on investing.